JAVA and DART programming languages: conceptual comparison - Afaf Mirghani Hassan (Institute of Advanced Engineering and Science, 2020)
This paper elaborates on the concepts of a new programming language “Dart”, which has been developed by Google and considered for future use. Here, we compare it to the most famous, real time, and updated language “Java”. This is to define similarities and differences between the two important languages, explain programs’ behavior, with a focus on investigating alternative implementation strategies and problem definitions. We used programming languages’ concepts and terminologies to compare between the main characteristics of the two languages, Dart & Java.